PENGARUH MOTIF BELANJA HEDONIC DAN MOTIF BELANJA UTILITARIAN TERHADAP KEPUASAN - Yuwono, Sapta Bagas Putra; Maduwinarti, Ayun; Mulyati, Diana Juni (Universitas 17 Agustus 1945 Surabaya, 2018)
This research entitled